Activities of the fourth wintering party at Asuka Station by the 31st Japanese Antarctic Research Expedition in 1990 - Kazuyuki Shiraishi (National Institute of Polar Research, 1992)
The wintering party at Asuka Station (71°31′34″S, 24°08′17″E, 930m a. s. l.) by the 31st Japanese Antarctic Research Expedition (JARE-31), consisting of 8 personnel, maintained Asuka Station continuously from December 25,1989 to December 26,1990. The main scientific programs of the party were the meteorological observation and studies of upper atmosphere physics. Other programs comprised geological investigation and search for meteorites in the Sor Rondane Mountains, and medical-biological studies, glaciological studies and logistic survey of the housing at Asuka Station and its vicinity. During the 1989/1990 summer season, Asuka Station was used as the base camp for the helicopter operation in the Sor Rondane Mountains. All programs were carried out successfully during the wintering and the Station was succeeded by JARE-32.